S SKRINING FITOKIMIA SERTA UJI AKTIVITAS ANTIOKSIDAN EKSTRAK BUNGA KETEPENG CINA (Senna alata (L.) Roxb.) DENGAN METODE DPPH - EKA RIA SAFITRI; Rohama Rohama; Putri Vidiasari D. (Jurnal Pelayanan Kefarmasian dan Sains, 2020)
Background: Indonesia has avarietyof plants that have potential as herbal medicines which are still unknown to many people, one of them is Chinese ketepeng flowers. Empirically in South Barito District, Central Kalimantan, Chinese ketepeng plants have been used for various diseases. Basedon this the researcher intend to conduct further research on antioxidant activity in the Chinese ketepeng flowers.   Objective: To determine secondary metabolite compounds and antioxidant activity contained in Chinese Ketepeng flower extract.   Methods: Thistype of research is experimental research, with Posttest Only Control Group Design. Extraction is done by maceration method. Phytochemical screening is done by color reagents and TLC. Test antioxidant activity with the DPPH method.   Results: 50 grams of Chinese ketepeng flower extraction with 9 L of 96% ethanol obtained thick extract of 35.34 gram. The results of phytochemical screening with color reagents and TLC extract of positive Chinese ketepeng flowers contain flavonoids, phenolic compounds,saponins and tannins. Antioxidant activity test results obtained by 185.037 ppm.   Conclusion:Chinese ketepeng extract contains secondary metabolites of flavonoids, phenolic, saponin and tannin compounds and obtained antioxidant activity of 185,037 ppm.Keywords:Antioxidants, Senna alata (L.) Roxb.flower, Phytochemicals.